Design and Implementation of an Internet of Things (IoT)-Based Smart Agriculture System for Soil Moisture Monitoring - Tata Sumitra (Pt. Anagata Sembagi Education, 2025)
Modern agriculture requires the use of technology to increase efficiency and productivity, particularly in water resource management. This study aims to design and implement an Internet of Things (IoT)-based smart farming system capable of monitoring soil moisture in real time to support irrigation efficiency. The method used in this study is a descriptive qualitative approach with a field study, which includes the device design process, system trials on agricultural land, and interviews and observations with users (farmers). The system is built using a soil moisture sensor connected to a microcontroller and sent to a web-based monitoring platform. The results show that the system is able to work effectively by providing real-time data that can be accessed anytime by farmers through digital devices. Farmers reported that it is more assisted in determining the right and efficient watering time, and saves water use by up to 20–30 percent. Furthermore, the simple system interface is considered easy to use even by farmers who are not familiar with technology. However, challenges such as limited internet connection and the need for device protection in the field are still encountered. This research makes a significant contribution to the development of low-cost technology-based farming systems that can be applied in rural areas. Thus, the integration of IoT in agricultural practices can be an innovative solution to support precision agriculture and sustainability.